Inteligência espiritual e saúde mental: um diálogo sob a perspectiva de profissionais da Psicologia - Oliveira Neto, Jorge Gomes de (2023)
Considering that many psychology professionals have difficulties understanding and dealing with the spiritual dimension of their practices, the purpose of this study was to gain a deeper understanding of their perspective on the construct of spiritual intelligence since the study of human intelligence has been part of their training and is, therefore, familiar to them. The hypothesis is that the construct of spiritual intelligence could generate an increased openness among these professionals to the spiritual component, which could then reflect on their practices. A semi-structured interview surveyed 20 psychology practitioners working in clinical settings. This research is exploratory-descriptive, concurrent with a quanti-qualitative approach, using content analysis as the method of analysis through Iramuteq software. Regarding the results, professionals interviewed defined spiritual intelligence as a capacity for seeking purpose, which significantly differed from a religious perspective, unlike when asked about spirituality. In terms of the correlation between spiritual intelligence and mental health, the majority believes in this correlation based on the notion that spirituality is intrinsic to human beings and, as a result, encompasses health. Besides, most of the interviewed professionals consider themselves development facilitators of their patients' or clients' spirituality, depending on their interests and demands. In conclusion, spiritual intelligence appears to be an alternative approach, especially when working with spirituality outside of a religious framework, turning it into a relevant construct to be applied and considered in psychological clinical practice.